A Possible Association of Staphylococcus Enterotoxin B-induced Asthma and Sinusitis - 刘涛 孔维佳 杨平常 王斌全 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
In order to gain insight into a possible association between chronic sinusitis and asthma, 85 patients with sinusitis and asthma underwent functional endoscopic sinus surgical treatment and serum antibodies and cytokines were measured. The results showed that 51 out of 85 patients with high serum anti-Staphylococcus enterotoxin B （SEB） antibody before treatment obtained satisfactory results for both sinusitis and asthma. The high level of Th2 cytokine IL-4 was down regulated to the levels of normal controls after sinus surgery. Thirty-four out of 85 patients did not show high serum anti-SEB antibody before sinus surgery and did not show much improvement in their asthmatic symptoms although sinusitis symptoms were resolved by sinus surgery. It was concluded that bacterial superantigen SEB （in the sinuses） might play a crucial role in the pathogenesis of lower airway hypersensitivity.